Empowering Sustainable Governance: The Role of Green Public Procurement and Certifications in Hungary - Majláth, Melinda; Reicher, Zsuzsánna Regina (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Agenda 2030 aim is to create a global framework for a sustainable economy in the EU. Green public procurements play a key role in this transformation in three aspects: (1) supports sustainable governance and management by embedding ESG principles into the decision-making process, also (2) it provides significant demand for environmental-friendly products and services and with that, motivation for green innovations. Thirdly, (3) completed procurements contribute to better environmental conditions improving quality of life. Green certifications support the process by providing credible, standardized proof that products and services meet the sustainability criteria. The aim of the chapter is to analyse how green public procurements have changed in Hungary in recent years and where the emphasis has shifted. The primary and secondary analyses are based on two sources from the Public Procurement Authority’s database. In addition to the development of the proportion of green public procurements, the study focuses on the importance of environmental certification as an expectation for bidders.